จากความศรัทธาอันแรงกล้าสู่แรงบันดาลใจในการสร้างสรรค์ ผลงานจิตรกรรมนามธรรม - ชารีฟ ตอเล็บ (คณะศิลปกรรมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2022)
In the disruptive world nowadays, social media is an important and influential factor on individuals thought, affective and mind. Social media overuse creates an apathy between human beings, increases criticizing and faulty social judgement, spread uncontrollable violence to young people. These situations isolate people from morality and be the cause of restraint and irrational behaviors. The research ‘From the Strongest Faith to an Inspiration for Abstract Painting Creation’ has the objective to present the concept of bringing back virtue of the goodness in people by representing artworks inspired from ‘Faith in God’ of the artist.The research process started with studying two contexts included; 1) the meaning of faith in religion and model persons and 2) the Abstract art and its painting process. From the literature review, the author found the connection between his strong faith in Islam and a kind of abstract painting in Islamic art. Especially for Islamic Art Calligraphy, one of the important Islamic art that is used to convey faith in Islam, inspired the artist to represent his depth belief in God with Abstract calligraphy painting in Arabic characters.